Konsep Manajemen Pendidikan Islam di Lembaga Pendidikan - Nahrowi, Mohamad; Permana, Hinggil; Sari, Nurlaela (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2022)
The holy book of muslims, namely Al-Qura’an Karim, Al-Qura’an for muslims serves as various intructions so that humans can carry out their mandate as caliphs on earth. Al-Qur’an has content that is very useful for humans, to obtain the contents of the content as a tool of guidance for muslims it is necessary to study the contents of the contents of the Al-Qur’an so that humans can more easily understand in complex discussing problems that have been discussed. Or what hasn’t happened. All things related to human life, as well as the existence of the universe have been listed in Al-Qur;anul Karim, including the problems carried out by humans to the activities carried out by humans on earth this case regarding the management of islamic education, it has been stated in the Al-Qur’an. The method used by the researcher is a qualitative research which only describes the concept of islamic education management. The data collection technique in this research is liberary research. The results of this study can be concluded that there are four concepts of islamic education management, namely : 1) felxible, 2) efficient and affective, 3) open, and 4) cooperative and participatory, wich are explained thoroughly and linked to explanations in the Al-Qur’an